Implementation of Nursing Ethical Principles in Action Services at Hewokloang Health Center: Qualitative Case Study - Gabriel Mane; Kristoforus Samson; Sisila Bernadetha Kristaviani3 (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The application of ethical principles is the main foundation in nursing practice to ensure patient safety, service quality, and protection of patients' rights, especially in first-level health services. However, findings suggest that the application of ethical principles, especially patient autonomy, still faces obstacles in daily nursing practice. The study purpose was to describe the application of the principles of nurse ethics in the action room of the Hewokloang Health Center. Materials and methods. The research used a Qualitative case study approach with in-depth thematic analysis. The informants consisted of six people consisting of three patients as the main informant and three nurses as supporting informants. Data was collected through in-depth interviews and in-depth thematic analysis, with stages of data reduction, data presentation, and conclusion drawn. Results. The results of the study showed that the application of most of the ethical principles of nurses in the action room of the Hewokloang Health Center was relatively good (>80%), especially beneficence, non-maleficence, justice, as well as aspects of professional responsibility and honesty. However, the principle of patient autonomy is still not optimal due to the limitations of therapeutic communication, so it is necessary to strengthen information provision and patient involvement in nursing decision-making. Conclusions. The application of the principles of nurse ethics in the Hewokloang Health Center action room is generally good, but it is still necessary to strengthen therapeutic communication to increase respect for patient autonomy and the quality of ethical nursing services.